Preoperative hydronephrosis is an independent protective factor of renal function decline after nephroureterectomy for upper tract urothelial carcinoma - Cheng, Pai-Yu; Lee, Hsiang-Ying; Li, Wei-Ming; Huang, Steven K.; Liu, Chien-Liang; Chen, I-Hsuan Alan; Lin, Jen-Tai; Lo, Chi-Wen; Yu, Chih-Chin; Wang, Shian-Shiang; Chen, Chuan-Shu; Tseng, Jen-Shu; et al. (Frontiers in Oncology, 2023)
Objectives: To evaluate the predictive role of pre-nephroureterectomy (NU) hydronephrosis on post-NU renal function (RF) change and preserved eligibility rate for adjuvant therapy in patients with upper tract urothelial carcinoma (UTUC). Patients and methods: This retrospective study collected data of 956 patients from the Taiwan UTUC Collaboration Group registry of 26 institutions. The patients were divided into two groups based on the absence or presence of pre-NU hydronephrosis. Estimated glomerular filtration rate (eGFR) was calculated pre- and post-NU respectively. The one month post-NU RF change, chronic kidney disease (CKD) progression, and the preserved eligibility rate for adjuvant therapy were compared for each CKD stage. Results: 385 (40.3%) patients without and 571 (59.7%) patients with pre-NU hydronephrosis were enrolled. The median post-NU change in the eGFR was significantly lower in the hydronephrosis group (-4.23 versus -12.85, p<0.001). Pre-NU hydronephrosis was associated with a lower CKD progression rate (34.9% versus 50.9%, p < 0.001) and was an independent protective factor for RF decline after covariate adjustment (OR=0.48, p<0.001). Patients with pre-NU hydronephrosis had a higher preserved eligibility rate for either adjuvant cisplatin-based chemotherapy (OR=2.11, 95%CI 1.43–3.12) or nivolumab therapy (OR=2.14, 95%CI 1.12–4.10). Conclusion: Pre-NU hydronephrosis is an independent protective predictor for post-NU RF decline, CKD progression, and eligibility for adjuvant therapy. With cautious selection for those unfavorably prognostic, non-metastatic UTUC patients with preoperative hydronephrosis, adjuvant rather than neoadjuvant therapy could be considered due to higher chance of preserving eligibility.